Pengaruh Latihan Wall Pass dan Drill Pass terhadap Ketepatan Passing Siswa Ekstrakurikuler Futsal (Jurnal Sosial Humaniora dan Pendidikan, 2022)
This study aims to determine the effect of wall pass and drill pass exercises on the passing accuracy of futsal extracurricular students. This type of research is classified as a quasi-experimental research with a two groups pretest-posttest design method. Data collection methods used are tests, measurements and treatments. The population in this study were all students who took part in the futsal extracurricular with a total of 47 students. The sample in this study were futsal extracurricular students who were still active as many as 20 students. The data analysis technique used is descriptive statistics, prerequisite test and t-test. The results showed that there was an increase in the passing accuracy of the futsal extracurricular students, namely for the wall pass group the average increase in the difference between pretest and posttest was 1.8 points, while for the drill pass group the average increase in the difference between pretest and posttest was 1.8 points. 3.5 points.